Anatomical and histochemical characterization of Dipteryx odorata and Taralea oppositifolia, two native Amazonian species - Silva, Paulo Marcos Ferreira da (2019)
Dipteryx odorata (Aubl.) Willd. and Taralea oppositifolia Aubl., Fabaceae: Dipterygeae, are two Amazonian species of great economic and pharmacological potential. The anatomy of these species, however, remains poorly studied. The aim of this work was to inventory leaf anatomical characteristics of D. odorata and T. oppositifolia and to locate and identify secretory structures and determine the main classes of metabolites they store. Vegetative branches were collected in Parque Ecológico de Gunma, Belém, state of Pará, Brazil. Some of the branches were destined for herborization while the remainder was submitted to standard protocols for anatomical analysis and histochemical tests. Both species were found to possess an unstratified epidermis, with D. odorata being amphistomatic and T. oppositifolia being hypostomatic, and dorsiventral mesophyll with spongy parenchyma and wide cellular space. The two species were also found to possess idioblasts and secretory cavities that produce a heterogeneous exudate consisting of polysaccharides, lipids, alkaloids and phenolic compounds. The species presented differences in leaf anatomy and chemical composition of the secretory structures, which may be useful in their differentiation.